CORRELATION BETWEEN TEACHERS’ COMPETENCE AND WAYS OF TEACHING TOWARD ENGLISH ACHIEVEMENT AMONG THE FIRST YEAR STUDENTS OF SMAN 1 GROGOL KEDIRI - A’midati, Tsalitsa Fithrotil (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aim of this study was to find out the correlation between teachers’ competence and ways of teaching toward English achievement among the first year students of SMAN 1 Grogol Kediri. The quantitative approach was used to design this research. The subject of this research was the first year students while the sample 134 students. The instruments were questionnaires and documentation. The techniques were partial and regression. From SPSS computation, the results which use partial correlation are 0.249and significance level at 5% (1-tailed) for the correlation between teachers’ competence and English achievement controlled by ways of teaching; 0.753and significance level at 1% or 0.00 (2-tailed) for the correlation between ways of teaching and English achievement controlled by teachers’ competence. While the result which uses regression is100.874.The significance level is 0.000(a)in ANOVA. It means that there is simultaneous significant correlation between three variables at the significant 1% because 0,000<0.001. It means that teachers’ competence and ways of teaching can predict English achievement. From the results, it is recommended that teachers should have good competence and variety ways of teaching to make students feel interested in the lesson and can increase their achievement in school.